A New Technique for Optimizing Resource Allocation and Data Distribution in Mobile Cloud Computing - Hung, Pham Phuoc; Bui, Tuan-Anh; Soonil, Kwon; Huh, Eui-Nam (Elektronika ir Elektrotechnika, 2016)
The emergence of mobile cloud computing (MCC) brings benefits to mobile users and cloud providers. However, due to the inherent limitations of the device such as battery life time, CPU and memory capacity, a mobile thin client device (e.g. smart phones, tablets, iWatch, Google Glass, etc) cannot meet the requirements of some demanding applications. To alleviate this limitation, the mobile device should cooperate with external resources to increase its performance. Recently, current research approaches have been unable to offer an efficient, seamless computing experience. In this paper, we present a comprehensive thin-thick client collaboration that involves conventional desktop or laptop computers, known as thick clients, by allowing the thin client to borrow resources from thick clients, particularly for optimizing data distribution and utilizing MCC resources to meet Service-Level Agreements, Quality-of-Service requirements and cloud service customers’ budget. Our work uses both numerical analysis and simulation to prove that our proposed architecture can improve resource allocation efficiency and achieve better performance than other existing approaches in some cases. DOI: http://dx.doi.org/10.5755/j01.eee.22.1.14113